SEMISSÍNTESE E AVALIAÇÃO ANTIFÚNGICA CONTRA FUSARIUM SOLANI F. SP. PIPERIS DE DERIVADOS DO EUGENOL - Maximino, Sarah Canal (2020)
Black pepper (Piper nigrum L.) has a high economic and export power due to the various forms of commercialization and the wide applicability of its essential oil. Meanwhile, Fusarium solani f. sp. piperis, a phytopathogen, is responsible for causing fusar